Analysis of Effective Learning Methods at SDN 222 Pasirpogor - Willy Alawiah; Muhibbin Syah; Bambang Samsul Arifin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to determine effective learning methods for grade 4 students of SDN 222 Pasirpogor. This type of research is descriptive qualitative research. The research was conducted in the even semester of the 2023/2024 school year. The subjects of the study were class 4 teachers and grade 4 students of SDN 222 Pasirpogor with a total of 26 students in class 4. The data collection method uses observation, interview, and documentation techniques. The data validity test uses source triangulation, engineering triangulation, and time triangulation which is then continued with data analysis which includes data reduction, data presentation, and conclusion drawing. The results showed that effective learning methods at SDN 222 Pasirpogor were the lecture method, the question and answer method, the assignment method, and the discussion method. Teachers are able to apply the method well and it is considered that the method applied is effective.